Moral Philosophy, Moral Expertise, and the Argument from Disagreement. (24th June 2015) - Cross, Ben
Abstract: Several recent articles have weighed in on the question of whether moral philosophers can be counted as moral experts. One argument denying this has been rejected by both sides of the debate. According to this argument, the extent of disagreement in modern moral philosophy prevents moral philosophers from being classified as moral experts. Call this the Argument From Disagreement (AD). In this article, I defend a version of AD. Insofar as practical issues in moral philosophy are characterized by disagreement between moral philosophers who are more or less equally well credentialed on the issue, non‐philosophers have no good reasons to defer to their views.